P068 LIPID PHOSPHATE PHOSPHATASE-3 (LPP3) DEFICIENCY INTENSIFIES INTESTINAL INFLAMMATION IN THE DSS MODEL OF ULCERATIVE COLITIS: ROLES OF LYSOPHOSPHATIDIC ACID AND LYMPHATIC/VASCULAR NETWORKS IN INFLAMMATORY GUT INJURY?. (18th January 2018) - Barzegar, M; Chandra, M; Yun, J Y; Harriss, P; Abdehou, S; Miryala, S; Boktor, M; Jordan, P A; Escalante-Alcalde, D; Panchatcharam, M; Alexander, J S
Abstract: Inflammatory bowel diseases (IBD), including Crohn's disease and ulcerative colitis (UC), affect more than 1 million people in the United States. Lysophosphatidic acid (LPA) is known to be a regulator of inflammation as well as governor of vascular structure function, and has been suggested to to be a regulator of lymphatic lineage and patterning. LPA levels are controlled both by the synthesis and catabolism of LPA by several enzymes especially lipid phosphate phosphatase-3 (LPP3). We previously reported remarkable intestinal blood and especially lymphatic vascularization in the 3% dextran sodium sulfate murine model of ulcerative colitis, which may be either adaptive or injurious depending on the phase of the model. In an effort to evaluate how suppression of LPA catabolism might influence both disease activity, gut injury, and vascular remodeling, we developed mouse models with a selective LPP3 deficiency in endothelial and hematopoietic cells. We achieved endothelial LPP3 (ERT2-LPP3) deficiency in adult mice using a tamoxifen-inducible Cre transgene under the control of the Tyrosine kinase Tek promoter. Previously, we have shown that ERT2-LPP3 mice exhibited a three-fold increase in circulating and tissue levels of LPA. These mice when subjected to 3% DSS colitis over 10 days, showed an intense and significantly increased gut injury characterized by significantly greater disease activity, weight loss, reduced overall survival, occult blood and fecal bleeding in KO animals on DSS; this group also showed a profound cecal enlargement. Gut lengths were significantly shorter in KO/DSS groups compared to DSS alone; gut weights were not be different. Histopathology, myeloperoxidase and lymphatic/blood vessel arrangements and vascular densities are currently under investigation to potentially link LPA, vascular remodeling and inflammation severity.